Next-generation personalised medicine for high-risk paediatric cancer patients – The INFORM pilot study. (September 2016) - Worst, Barbara C.; van Tilburg, Cornelis M.; Balasubramanian, Gnana Prakash; Fiesel, Petra; Witt, Ruth; Freitag, Angelika; Boudalil, Miream; Previti, Christopher; Wolf, Stephan; Schmidt, Sabine; Chotewutmontri, Sasithorn; Bewerunge-Hudler, Melanie; et al.
Abstract: The 'Individualized Therapy for Relapsed Malignancies in Childhood' (INFORM) precision medicine study is a nationwide German program for children with high-risk relapsed/refractory malignancies, which aims to identify therapeutic targets on an individualised basis. In a pilot phase, reported here, we developed the logistical and analytical pipelines necessary for rapid and comprehensive molecular profiling in a clinical setting. Fifty-seven patients from 20 centers were prospectively recruited. Malignancies investigated included sarcomas (n = 25), brain tumours (n = 23), and others (n = 9). Whole-exome, low-coverage whole-genome, and RNA sequencing were complemented with methylation and expression microarray analyses. Alterations were assessed for potential targetability according to a customised prioritisation algorithm and subsequently discussed in an interdisciplinary molecular tumour board. Next-generation sequencing data were generated for 52 patients, with the full analysis possible in 46 of 52. Turnaround time from sample receipt until first report averaged 28 d. Twenty-six patients (50%) harbored a potentially druggable alteration with a prioritisation score of 'intermediate' or higher (level 4 of 7). Common targets included receptor tyrosine kinases, phosphoinositide 3-kinase–mammalian target of rapamycin pathway, mitogen-activated protein kinase pathway, and cell cycle control. Ten patients received a targeted therapy based on these findings, with responses observed in some previously treatment-refractory tumours. Comparative primary relapse analysis revealed substantial tumour evolution as well as one case of unsuspected secondary malignancy, highlighting the importance of re-biopsy at relapse. This study demonstrates the feasibility of comprehensive, real-time molecular profiling for high-risk paediatric cancer patients. This extended proof-of-concept, with examples of treatment consequences, expands upon previous personalised oncology endeavors, and presents a model with considerable interest and practical relevance in the burgeoning era of personalised medicine. Highlights: Germany-wide personalised medicine study for high-risk paediatric cancer patients. Comprehensive sequencing and analysis is feasible in clinically relevant time frame. Half of patients across entities harbored a reasonable confidence druggable target. Cases of clinical response to targeted agents demonstrate proof of principle. This model can expand paediatric access to molecular profiling and targeted therapies.